Frequency of Nonalcoholic fatty pancreatic disease (NAFPD) in patients with carcinoma pancreas presenting for upper abdominal EUS in a tertiary care center - Sajida Qureshi; Memon, Fahad; Chisti, Noorulain; Ghazanfar, Shahriyar; Quraishy, Mohammad Saeed (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of nonalcoholic fatty pancreatic disease in patients with carcinoma pancreas presenting for upper abdominal endoscopic ultrasound. Method: The prospective cross-sectional study was conducted in the Endoscopy Suite of Surgical Unit 4, Civil Hospital, Karachi, from October 2019 to September 2020, and comprised patients presenting for endoscopic ultrasound. Patients were divided into Group A comprising carcinoma pancreas patients, and Group B having non-carcinoma pancreas patients. Fatty pancreas was identified by hyperechogenicity on endoscopic ultrasound. Data was analysed using SPSS 19. Result: Of the 68 patients, 44(64.7%) were male and 24(35.3%) were females. The overall mean age was 49.9±13.82 years (range: 16-80 years). There were 35(51.5%) patients in Group A and 33(48.5%) in Group B. The frequency of nonalcoholic fatty pancreatic disease was 18(26.5%) and 15(83.3%) of them were male subjects (p=0.04). Group A had 12(34.28%) subjects with nonalcoholic fatty pancreatic disease compared to 6(18%) in Group B (p=0.11). Conclusion: Nonalcoholic fatty pancreatic disease was frequently seen in carcinoma pancreas patients undergoing endoscopic ultrasound compared to non-carcinoma pancreas patients. Most of the patients affected were males. Key Words: Nonalcoholic fatty pancreas, NAFPD, Fatty pancreas, Steatopancreatitis, Pancreatic fibrosis.